Recurrent Syncope During Migraine Attacks - Dias da Costa, Mariana; Nunes Vicente, Beatriz; Dourado Sotero, Filipa; Pavão Martins, Isabel (Acta medica portuguesa, 2025)
Migraine is a cyclic condition with attacks consisting mainly of intense headaches, sensory intolerance, and nausea or vomiting. Loss of consciousness during attacks is often attributed exclusively to a neurally mediated reflex to pain, although it may also be due to migraine’s autonomic impairment, with cardiac conduction abnormalities, probably in relation to a degree of reduced sympathetic function. We report the case of a 51-year-old woman presenting episodes of syncope exclusively after vomiting during migraine attacks. A 24-hour Holter monitoring performed during a migraine attack disclosed an intermittent complete atrioventricular block coincident with an episode of syncope. The patient was implanted with a pacemaker without further syncopes on subsequent attacks. This case highlights the importance of clinical suspicion and investigation of syncope during migraine attacks. Recurrent syncope during migraine should not be attributed to pain to avoid misdiagnosis and ensure the treatment of other important causes of syncope.